Verletzungen am lateralen Kapselbandapparat des Sprunggelenks - eine Übersicht - Lohrer, H.; Alt, W.; Gollhofer, A.; Rappe, B. (Deutsche Zeitschrift für Sportmedizin, 2000)
Preventive therapeutic and rehabilitational concepts for ligamentous ankle injuries have frequently changed in the last decades. Recent investigations have been related more and more to active mechanism of functional ankle joint stabilization while previous work concentration mainly on passive and therefore mechanical aspects. Some risk factors predisposing for ankle injuries have been evaluated. In this context subjective feeling of instability, measured by visual analogie scale (VAS) seems to be most important and can be easily assessed. recently, a new device forcomülex and simultaneous investigation of actibe and passive reactions, following and injury simulation , was indroduced. Relative neuromuscular stimulation is proven for tape, for special ankle orthroses and for proprioceptive training. A comparative parameter (PAR = proprioceptive amplification ratio) was calculated. On the basis of current knowledge on ankle sprains a treatment algorithm can be established. Thus, any lateral ankle ligament injury should be treated according to a clearly outlined protocol based on scientific standards. According ti his, surgery (direct suture, capsular reefing or periosteal flap stabilization) is demanded only for second stage ruptures and fpr chronical instabilities, that is for patients who have previously suffered fear of giving way. Dtsch. Z. Sportmed., 51(2000)6, S. 196-203